Electronically Tunable Transparent Conductive Thin Films for Scalable Integration of 2D Materials with Passive 2D–3D Interfaces (Adv. Funct. Mater. 21/2022). (19th May 2022) - Grünleitner, Theresa; Henning, Alex; Bissolo, Michele; Kleibert, Armin; Vaz, Carlos A.F.; Stier, Andreas V.; Finley, Jonathan J.; Sharp, Ian D.
Abstract : Passive 2D–3D Interfaces In article number 2111343, Alex Henning, Ian D. Sharp, and co‐workers develop a novel transparent and conductive support structure for the scalable integration and direct growth of 2D materials. The structure comprises a nanocrystalline carbon layer coated with nanometer‐thin alumina and provides an electronically passive 2D–3D interface, which enables facile interfacial charge transport and significantly enhances the photoluminescence of monolayer MoS2 .